Effect of Thyme Essential Oil on Vase Life of Two Carnations (Dianthus caryophyllus L.) Cultivars. Issue 3 (2nd April 2016) - Amini, Sheno; Arab, Mostafa; Rahemi, Majid; Rahimi, Abdol Rahman; Garmakhany, Amir Daraei
Abstract: Two experiments carried out in order to study the influence of thyme essential oil on longevity of two cultivars of carnation ( Dianthus caryophyllus L.) flowers. The treatments include control (distillation water) and concentrations 250, 500 and 1000 ppm of TEO for the first experiment and concentrations 0, 50, 100, 150 and 200 ppm of TEO for the second experiment. Results showed that concentrations up to 250 ppm of TEO decreased the vase life at both cultivars of carnation. In lower concentrations, Beaumonde cultivar had a weak reaction than TEO in vase life, while application of 200 ppm of TEO significantly extended longevity in Sensi cultivar by 2.34 days. Also the relative fresh weight and total solution uptake for both cultivar, relative extension of flowers for Beaumonde cultivar and content of anthocyanin in Sensi cultivar were not affected significantly by treatments. Concentrations 50 and 200 ppm of TEO in Sensi cultivar had a positive relative extension of flower (diameter of flower) and showed significant difference than control. 200 ppm TEO increased the anthocyanin in Beaumonde cultivar significantly. The diameter of flowers as index for extension or rolling had a significant positive correlation with vase life in both cultivars. The Correlation of vase life with relative fresh weight and total solution uptake were positive and insignificant; in addition, there are insignificant negative correlations between fresh weight and solution uptake in both cultivars.